Caracterización microbiana de aislados del suelo y de la microbiota intestinal de escarabajos peloteros de la Reserva Madrigal del Podocarpus, Loja - Bravo Landacay, Katherine Lizbeth (2024)
Soil is an important ecosystem in which different bacterial species play a crucial role as bioindicators of its ecological and evolutionary behavior. This study is characterized and identified both morphologically and metabolically bacterial communities in the intestinal microbiota of dung beetles (Coleoptera: Scarabainae) and the soil from three ecological succession states (natural forest, grassland, and burned area) in El Madrigal del Podocarpus Reserve. The morphological identification of bacterial colonies was carried out by observing macroscopic characteristics on three selective media: MacConkey Agar, LB Agar, and cetrimide Agar. Additionally, bacterial cells were identified through Gram staining and microscopic observation. Biochemical tests such as catalase, mannitol, citrate, and Triple Sugar Iron (TSI) were applied for the identification of certain metabolic reactions of the bacteria. Bacterial strains obtained in the characterization of bacterial consortia from beetle intestine samples and soil samples were associated with 15 different possible bacterial genera. It was concluded that there is variation among some of the identified genera in relation to the three states of ecological succession. However, four genera with similar presence were identified in all three sampled areas: Pseudomonas, Staphylococcus, Bacillus, and Escherichia. These genres have potential for plant growth and are involved in regeneration processes, indicating an active recovery process in the studied areas.